Reflections of coloproctology history in postage stamps - Samuolis, Remigijus (Lietuvos chirurgija, 2015)
Coloproctology is a branch of medicine dealing with pathology of the colon, rectum and anus and colorectal surgery. Thematic or topical philately is the study of what is depicted on the stamps. There are lot of popular subjects and the stories of how particular images of stamps came to be used. This article is an attempt to show that even such a special subject as a history of coloproctology could be told through postage stamps. It is an overview of medical history from the antiquity to the present, interesting facts about famous proctological sufferers some reflections of proctological theme in literature. Although an article does not reflect an entire history of coloproctology, it presents the major roots and development stages of this speciality. All the stamps and philatelic material shown are from my collection.